1987
DOI: 10.1051/rnd:19870302
|View full text |Cite
|
Sign up to set email alerts
|

Effet d'une carence hydrique prolongée sur la croissance pondérale et sur le métabolisme hydrique chez un rongeur Gerbillidé (Meriones shawi shawi)

Abstract: Summary. Effect of prolonged water deprivation on weight gain and water metabolism in sub-desert rodents (Meriones shawi shawil.The effect of prolonged water deprivation, applied progressively since weaning, was studied on body weight in growing sub-desert rodents (Meriones shawi l . Then, water metabolism, food consumption and kidney weight were measured in these adults animals.During partial water deprivation the weight curve was similar to that of controls, whereas with total water deprivation three differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…The changes in body weight under prolonged dehydration previously studied in growing Meriones shawi shawi (Sahni et al 1987) are related to the changes in food intake demonstrated in the present study. Despite a reduction in food intake, the animals subjected to partial water deprivation showed an increase in their body weight in the same proportion as hydrated animals.…”
Section: Kidney Weightsupporting
confidence: 70%
See 1 more Smart Citation
“…The changes in body weight under prolonged dehydration previously studied in growing Meriones shawi shawi (Sahni et al 1987) are related to the changes in food intake demonstrated in the present study. Despite a reduction in food intake, the animals subjected to partial water deprivation showed an increase in their body weight in the same proportion as hydrated animals.…”
Section: Kidney Weightsupporting
confidence: 70%
“…In previous work (Sahni et al 1987) w e have shown that prolonged dehydration during growth alters body weight. O n the other hand, w e have also demonstrated that adult jirds deprived of water since weaning are able to maintain their water balance in equilibrium.…”
Section: Introductionmentioning
confidence: 92%